Gas Chromatography-Mass Spectral Analysis of Paint Thinner - Narayan Sinha, Sukesh; Zadi, S.S. (Asian Journal of Chemistry, 2010)
Gas chromatography-mass spectroscopy was used for the confirmation of volatile organic compounds presence in paint thinner. The toxic compounds are toluene, xylene, ethyl benzene, 2,4-dimethyl heptane, cyclohexane propanol, 1-(methyl ethyl)cyclohexane, propyl benzene, 1-ethyl-3-methyl benzene, p-ethyl toluene, 2,3-trimethyl benzene, ethyl-2-methyl benzene, heptyl cyclohexane, 1-methyl-3-propyl benzene, diethyl benzene, 4-ethyl octane, napthalene and 3-methyl decane were present in thinner. These all compounds were confirmed using retention time parameter, molecular ion peak, base peak and other characteristic peak using National Institute of Science Technology (NIST) library search. The percentage composition of thinner has been also explained.